2018
DOI: 10.1111/adj.12596
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of major defects of the jaws

Abstract: Prosthetic replacements in the 19th and early 20th century were superseded by pedicled flaps and obturators. These have subsequently been superseded by free tissue transfer which currently is the mainstay of reconstructive jaw surgery. Although malignant and benign processes of the jaws are the predominant cause of segmental defects, a significant proportion still occurs due to trauma, or even iatrogenic causes such as radiotherapy. The varied aetiologies demand a nuanced approach to reconstruction and althoug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 11 publications
0
45
0
Order By: Relevance
“…The reconstruction of the surgical defect is then completed and this is well described in the following paper in this supplement …”
Section: Surgerymentioning
confidence: 99%
“…The reconstruction of the surgical defect is then completed and this is well described in the following paper in this supplement …”
Section: Surgerymentioning
confidence: 99%
“…1 Advances in reconstructive surgery in recent decades have resulted in the use of vascularized bone grafts (VBGs) as the ideal contemporary choice for reconstruction. 2 A variety of donor sites, including free fibula flap (FFF), deep circumflex iliac artery flap (DCIA), scapula, and radial forearm free flaps (RFFFs), can be used and have been found to be highly successful. 3 In addition to these commonly used flaps, the medial femoral condyle has been utilized specifically for maxillary defects.…”
Section: Introductionmentioning
confidence: 99%
“…One of the ultimate aims of reconstruction with VBGs is to create a sound bony foundation for osseointegrated implants to support a dental prosthesis, to further restore masticatory function, speech, and aesthetics. 2 There has been some investigation into the success of implants into VBG's examining factors such as timing of implant placement, 5 patient satisfaction in maxillary reconstructions, 6 the impact of extra-oral skin in peri-implant disease, 7 and a comparison of implants in patients with cancer who received a fibula free flap compared to a soft tissue flap. 8 A systematic review of implants in bone flaps concluded that the timing of implant placement and radiotherapy are factors affecting survival, although there was limited evidence.…”
Section: Introductionmentioning
confidence: 99%
“…Reconstruction of the mandible is always a challenging clinical task due to the complexity of anatomy, function, and aesthetic role [12]. In particular, restoring form and function plays a pivotal role [13].…”
Section: Discussionmentioning
confidence: 99%